Perencanaan Anggaran Biaya Sistem Jaringan Distribusi Air Bersih Perumahan Aloha ke Jl. Raya S. Parman Sidoarjo - Zettyara, Devi; Safitri, Mona Shinta (Publikasi Indonesia, 2025)
Access to clean water is an important indicator of community quality of life. This research aims to analyze budget planning for clean water distribution network systems from Aloha Housing to Jl. Raya S. Parman Sidoarjo in supporting Umbulan Regional SPAM operations. The research methodology uses a descriptive quantitative approach with Work Unit Price Analysis (AHSP) based on Sidoarjo Regency HSPK and current material price references. Primary data was obtained through field surveys and measurement of existing conditions, while secondary data included planning drawings and technical specifications. The results showed a total Budget Plan (RAB) of IDR 5,022,504,000 for a 2,827 km network length with a cost per meter of IDR 1,614,896. The cost structure is dominated by pipe and accessory procurement (57.20%), preparatory work (8.83%), and earthwork (8.32%). Sensitivity analysis revealed that 300 mm PVC pipes contribute 54.59% to total costs with high sensitivity to material price fluctuations. Benchmarking with PUPR HSPK shows positive deviations of 5-11% which can be explained by local factors. Project cost-effectiveness shows a cost per capita served of IDR 125,563/person with a 20-year projected ROI of 12.5% and a payback period of 8.2 years, indicating good economic feasibility. This research recommends optimization through integrated regional procurement, development of technical guidelines for construction methods, and improved spatial planning coordination to reduce inefficiency. The findings support achieving the 2030 universal clean water access target with a cost-effective and sustainable approach.